Value aspect of text formation: the dynamics of meaning - Kyrkunova, Larisa S. Tikhomirova, Nataliya V. Danilevskaya, Elena A. Bazhenova, Larisa G.; Karpova, Tatiana B. (Opción, 2020)
The paper’s objective is to identify the characteristics of the formation and expression of new knowledge in a scientific text. The leading research method is functional-stylistic. The study revealed that the alternation of components of old and new knowledge is the mechanism of text formation, reflecting the logical sequence of cognitive actions directed on the substantiation of new knowledge. In conclusion, the result of the textualization of cognitive examination appears in the text in the form of cognitive-evaluative actions such as explanation, specification, generalization, definition, consequence, conclusion, etc.; in the dynamics of knowledge representation, different validation actions are often syncretic.